The efficacy and safety of pulse vs. continuous therapy for dermatophyte toenail onychomycosis. (15th December 2019) - Gupta, A.K.; Stec, N.; Bamimore, M.A.; Foley, K.A.; Shear, N.H.; Piguet, V.
Abstract: Background: Onychomycosis is a chronic, fungal infection of the nails. Complete cure remains challenging, but oral antifungal medications have been successful in managing the fungus for a significant proportion of patients. Treatment with these drugs can be continuous or intermittent, albeit the evidence on their relative efficacies remains unclear. Objective: To determine the relative effectiveness and safety of pulse versus continuous administration, of three common oral therapies for dermatophyte onychomycosis, by conducting multiple‐treatment meta‐analysis. Methods: This systematic review and network meta‐analysis compared the efficacy (as per mycological cure) and adverse event rates of three oral antifungal medications in the treatment of dermatophyte toenail onychomycosis, namely terbinafine, itraconazole and fluconazole. A total of 30 studies were included in the systematic review, while 22 were included in the network meta‐analysis. Results: The likelihood of mycological cure was not significantly different between continuous and pulse regimens for each of terbinafine and itraconazole. Use of continuous terbinafine for 24 weeks – but not 12 weeks – was significantly more likely to result in mycological cure than continuous itraconazole for 12 weeks or weekly fluconazole for 9–12 months. Rank probabilities demonstrated that 24‐week continuous treatment of terbinafine was the most effective. There were no significant differences in the likelihood of adverse events between any continuous and pulse regimens of terbinafine, itraconazole and fluconazole. Drug treatments were similar to placebo in terms of their likelihood of producing adverse events. Conclusion: More knowledge about the fungal life cycle and drugs' pharmacokinetics in nail and plasma could further explain the relative efficacy and safety of the pulse and continuous treatment regimens. Our results indicate that in the treatment of dermatophyte toenail onychomycosis, the continuous and pulse regimens for terbinafine and itraconazole have similar efficacies and rates of adverse events.